Abdominal Wall Endometrioma: Ultrasonographic Features and Correlation with Clinical Findings - Aynur Solak; Berhan Genç; Neslin Şahin; Seyhan Yalaz; Taylan Özgür Sezer; İlhami Solak (Balkan Medical Journal, 2013)
Background: The diagnosis of abdominal wall endometrioma (AWE) is often confused with other surgical conditions. Certain factors relating to knowledge of the clinical history of the disease make correct diagnosis and treatment difficult.